Arrhythmia exacerbation after post-infarction ventricular tachycardia ablation: prevalence and prognostic significance. Issue 11 (23rd August 2020) - Siontis, Konstantinos C; Kim, Hyungjin M; Vergara, Pasquale; Peretto, Giovanni; Do, Duc H; de Riva, Marta; Lam, Anna; Qian, Pierre; Yokokawa, Miki; Jongnarangsin, Krit; Latchamsetty, Rakesh; Jais, Pierre; et al.
Abstract: Aims : Catheter ablation is an effective treatment for post-infarction ventricular tachycardia (VT). However, some patients may experience a worsened arrhythmia phenotype after ablation. We aimed to determine the prevalence and prognostic impact of arrhythmia exacerbation (AE) after post-infarction VT ablation. Methods and results : A total of 1187 consecutive patients (93% men, median age 68 years, median ejection fraction 30%) who underwent post-infarction VT ablation at six centres were included. Arrhythmia exacerbation was defined as post-ablation VT storm or incessant VT in patients without prior similar events. During follow-up (median 717 days), 426 (36%) patients experienced VT recurrence. Events qualifying as AE occurred in 67 patients (6%). Median times to VT recurrence with and without AE were 238 [interquartile range (IQR) 35–640] days and 135 (IQR 22–521) days, respectively ( P = 0.25). Almost half of the patients (46%) who experienced AE experienced it within 6 months of the index procedure. Patients with AE had had longer ablation times during the ablation procedures compared to the rest of the patients (median 42 vs. 34 min, P = 0.02). Among patients with VT recurrence, the risk of death or heart transplantation was significantly higher in patients with than without AE (hazard ratio 1.99, 95% CI 1.28–3.10; P = 0.002) after adjusting for age, gender, ejection fraction, cardiac resynchronization therapy, post-ablation non-inducibility, and post-ablation amiodarone use. Conclusion : Arrhythmia exacerbation after ablation of infarct-related VT is infrequent but is independently associated with an adverse long-term outcome among patients who experience a VT recurrence. The mechanisms and mitigation strategies of AE after catheter ablation require further investigation.